Photon shifting and trapping in perovskite solar cells for improved efficiency and stability - Haque, Sirazul (2024)
Funding Information: The work was financed by national funds from FCT (Fundação para a Ciência e Tecnologia, I.P.) in the scope of the projects LA/P/0037/2020, UIDP/50025/2020, and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling, and Nanofabrication - i3N, and the FCT, I.P. project SpaceFlex (2022.01610.PTDC), as well as by M-ECO2 project (Industrial cluster for advanced biofuel production, Ref. C644930471-00000041) co-financed by PRR - Recovery and Resilience Plan of the European Union (Next Generation EU). This work was also developed within the scope of the projects: CICECO - Aveiro Institute of Materials, UIDB/50011/2020, UIDP/50011/2020, and LA/P/0006/2020 financed by national funds through the FCT, I.P. (PIDDAC). S.H. acknowledges the support from FCT, I.P. through the AdvaMTech Ph.D. program scholarship PD/BD/143031/2018. S.H. and S.Y. acknowledge the support of the SRP-JRP project (non-EE046). M.A. also acknowledges the support from FCT, I.P. through the Ph.D. scholarship grant SFRH/BD/148078/2019. Publisher Copyright: © The Author(s) 2024.